Trans-arterial positive ICG staining-guided laparoscopic liver watershed resection for hepatocellular carcinoma - Qian, Xinye; Hu, Wang; Gao, Lu; Xu, Jingyi; Wang, Bo; Song, Jiyong; Yang, Shizhong; Lu, Qian; Zhang, Lin; Yan, Jun; Dong, Jiahong (Frontiers in Oncology, 2022)
Introduction: Anatomical liver resection is the optimal treatment for patients with resectable hepatocellular carcinoma (HCC). Laparoscopic Couinaud liver segment resection could be performed easily as liver segments could be stained by ultrasound guided Indocyanine green (ICG) injection into the corresponding segment portal vein. Several smaller liver anatomical units (liver watersheds) has been identified (such as S8v, S8d, S4a, S4b). However, since portal veins of liver watersheds are too thin to identify under ultrasound, the boundaries of these liver watersheds could not be stained intraoperatively, making laparoscopic resection of these liver watersheds demanding. The digital subtraction angiography (DSA) could identify arteries of liver watersheds with a diameter less than 2 mm. Yet, its usage for liver watershed staining has not been explored so far. Purpose: To explore the possibility of positive liver watershed staining via trans-arterial ICG injection under DSA examination for navigating laparoscopic watershed-oriented hepatic resection. Methods: We describe, in a step-by-step approach, the application of trans-arterial ICG injection to stain aimed liver watershed during laparoscopic anatomical hepatectomy. The efficiency and safety of the technique is illustrated and discussed in compare with the laparoscopic anatomical liver resection via ultrasound guided liver segment staining. Results: 8 of 10 HCC patients received successful trans-arterial liver watershed staining. The successful rate of the trans-artery staining approach was 80%, higher than that of ultrasound guided portal vein staining approach (60%). Longer surgical duration was found in patients underwent trans-artery staining approach (305.3±23.2 minutes vs 268.4±34.7 minutes in patients underwent ultrasound guided portal vein staining approach, P = 0.004). No significant difference was found in major morbidity, reoperation rate, hospital stay duration, 30 day and 90 day mortality between the 2 groups. Conclusions: Trans arterial ICG Staining is safe and feasible for staining the aimed liver watershed, navigating watershed-oriented Hepatic resection under Fluorescence Laparoscopy for surgeons.